Revisiting Jadid Pedagogy for Sustainable Development Goals (SDGs): A Conceptual Framework for Digital Educational Governance - Rukhsatoy Sunnatullaevna Shamsullaeva; Shakhnoz Khikmatovna Samieva; Gulnoza Odiljon Khamrakulova; Dilnoza Jurayevna Kuvatova; Gulzoda Toshtemirovna Boymurodova; Maftuna Karimovna Toshtemirova; Mehriniso Husniddin Ergashova (ASEAN Journal of Educational Research and Technology, 2026)
This study revisits Jadid pedagogy as a historical educational movement that can inform contemporary digital educational governance and Sustainable Development Goals (SDGs). Using a conceptual research design supported by systematic literature review principles, the study analyzes historical Jadid educational mechanisms and contemporary literature on educational leadership, digital governance, self-efficacy, and competency-based learning. Jadid principles, including phonetic learning, visible knowledge, structured schooling, and ethical modernization, can be translated into digital governance, immersive learning, and education manager development. The study proposes a Jadid-Digital Educational Governance Model for improving inclusive, culturally grounded, and innovation-oriented education.